GREEN BONDS: WORLD’S EXPERIENCES, CURRENT STATUS AND PROPOSAL FOR IMPROVING VIETNAMESE LAW - Thai, Luu Quoc (American International Journal of Social Science Research, 2021)
Vietnam is a developing country, often adversely affected by environmental pollution and climate change. One of the main reasons leading to this situation is outdated production technologies, which is not environmentally friendly. This situation has been causing serious impacts on the economy and society of this country. According to the experience of developed countries and to fulfill national commitments on the environment, investment projects in production and business are encouraged to be implemented in an environmentally friendly manner. To do this, investors, especially businesses, need to mobilize a certain financial source to equip facilities and production technologies that cause less pollution. Among financial instruments, green bonds are an emerging factor applied by many countries around the world and Vietnam is also ready to test it. However, up to now, the issuance of green bonds in Vietnam has not been possible because of the lack of a complete legal mechanism. So, this article will analyze Vietnamese law on this issue on the basis of learning experiences from other countries to come up with a complete solution for Vietnam.